Grazing reverses climate-induced soil carbon gains on the Tibetan Plateau - Shuai Ren; Tao Wang; Xinhui Ji; Liang Wei; Jianjun Wei; Yingfang Cao; Jinzhi Ding (Nature Communications)
Abstract Soil carbon stocks on the Tibetan Plateau are widely considered to be increasingly threatened by drastic climate warming and intensified livestock grazing. But it remains elusive due to unconstrained model projections. Here we integrate large-scale soil campaigns, soil incubation with paired grazing experiments to project impacts of climate change and grazing on soil carbon stocks in a three-pool soil carbon model. While Tibetan soils will act as a carbon sink, over half of the gains occur in active or unprotected pools, making them vulnerable to extreme events and grazing. Although thermokarst processes may not reverse this trend, continued livestock grazing at current levels, or even a transition to a forage-livestock balanced state, could nearly offset climate-induced benefits. We highlight the critical need to optimize grazing to sustain soil carbon sinks on the Tibetan Plateau, and emphasize the importance of incorporating grazing impacts on soil carbon stocks into Earth system models.